Software Engineering Meets Services and Cloud Computing. - Yau, Stephen; An, Ho (Computer (00189162), 2011)
Service-oriented software engineering incorporates the best features of both the services and cloud computing paradigms, offering many advantages for software development and applications, but also exacerbating old concerns.